Successful Endovascular Repair of a Ruptured Popliteal Artery Aneurysm: A Case Report and Literature Review. (16th March 2020) - Muir, Duncan; Kulkarni, Sachin R.
Abstract : Introduction . It is rare for a popliteal artery aneurysm (PAA) to present with rupture. This case reports a longer-term success in the management of a large ruptured popliteal artery aneurysm with an endovascular approach, with a literature review of management of such cases. Case Report . An 80-year-old man presented to the accident and emergency department with pain and swelling behind the left knee and at the back of the thigh. An ultrasound scan and subsequent CT angiogram revealed a large 9.4 cm ruptured PAA. The patient had significant comorbidities deeming him unfit for a major surgical intervention of drainage of haematoma and exclusion bypass. Therefore, he underwent urgent endovascular treatment of the ruptured PAA with a covered stent graft. A follow-up duplex scan at 1 year showed a patent stent with no evidence of endoleak, and the patient remained asymptomatic. A clinical follow-up at 18- and 24-month postprocedure showed a patent stent graft and complete resolution of haematoma. Conclusion . Whilst open repair with exclusion bypass may still be a treatment of choice, an endovascular approach is both safe and effective in the management of a ruptured PAA in an unfit patient with an acceptable longer-term outcome.